2011
DOI: 10.1063/1.3530289
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orientations and interfacial structure of C60 on Pt(111)

Abstract: Molecular orientations and assembled structures of C(60) molecules on Pt(111) have been characterized by low-temperature scanning tunneling microscopy for coverage between 0.1 ML and 1.5 ML. At room temperature, C(60) molecules preferentially decorate the steps and nucleate into single layer islands (SLIs) with hexagonal close-packed structures upon increasing coverage. C(60) islands comprise two differently oriented C(60)∕Pt(111)-(√13 × √13) R13.9° phases, in which five types of molecular orientation of C(60)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 39 publications
5
57
0
Order By: Relevance
“…4 As Table III exhibits, DFT and LEED agree closely, the two phases have almost identical local adsorption structures, and they show a strong covalent C-Pt bond character. 14 These results agree with the model proposed in a recent scanning tunneling microscopy study, 12 while providing much more information and reliability. In this structure, C 60 sits on top of the Pt vacancy with hexagon down and forms six C-Pt covalent bonds with the six Pt atoms surrounding the vacancy.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…4 As Table III exhibits, DFT and LEED agree closely, the two phases have almost identical local adsorption structures, and they show a strong covalent C-Pt bond character. 14 These results agree with the model proposed in a recent scanning tunneling microscopy study, 12 while providing much more information and reliability. In this structure, C 60 sits on top of the Pt vacancy with hexagon down and forms six C-Pt covalent bonds with the six Pt atoms surrounding the vacancy.…”
Section: Resultssupporting
confidence: 82%
“…It has moreover been observed that annealing at 500 K cannot partially change the √ 13 phase to the 2 √ 3 phase, while such changes may occur at even higher temperatures. 12 Based on the determined geometric structures, we further study the electronic structures of C 60 in these two phases by DFT calculations. To understand the effects of C 60 -C 60 and Pt-C 60 interactions, Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations